Role of Irrigants in Endodontics - Prabjot Kaur (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Irrigation is a key part of successful root canal treatment as it fulfils several important mechanical, chemical and (micro) biological functions including the healing of periapical tissues. It is the only way to reach and impact those areas of the root canal wall which are not touched by mechanical instrumentation. The initial and primary endodontic treatment (rootcanal treatment) goal must be to optimize root canal disinfection and to prevent reinfection. All over the years many materials have been used to serve as endodontic irrigants particularly sodium hypochloride and EDTA. However there are also other solutions available which can be used for the purpose of irrigation. So, in this article we will narrate different types of irrigating solutions with their specifics, requirements, which can be used in future endodontic practice, and their advantages and limitations.